Climatic aspects of sustainable development of the Republic of Tyva - Sambuu Anna; Sevastyanov Vladimir; Ondar Minchimaa (E3S Web of Conferences)
The results of the work of the meteorological station in Kyzyl for 135 years are considered. The features of global climate warming in mountain basins are largely represented. To trace the dynamics of temperature changes over a longer period, the results of observations of changes in the average monthly and annual temperatures of the low-lying air of the city of Kyzyl in the Tuva basin and at the nearest meteorological station in the city of Minusinsk in the basin of the same name were used. The distance between them is about 350 km. Data analysis from 1885 to 2020 He showed that in the conditions of the mountainous climates of Siberia, it is not enough to focus on the generalizing results of changes in climatic conditions, fluctuations in the temperature regime, which may exceed the rate of modern warming in the polar regions. In this regard, when conducting climate monitoring of environmental facilities, it is important to assess the regional features of climate change.